Wave-in-Deck Force on Fixed Jacket Platforms by Silhoutte Method and Detailed Component Method - Pangestu, L.A. (Springer, 2020)
Wave-in-deck creates extra forces to the platform by increasing its moment arm which cause instability in terms of overturning. Fixed offshore platforms are generally not intended to withstand the substantial forces produced by wave-in-deck loads. Nonetheless, the requirement to accurately predict the magnitude of wave-in-deck forces and the platform global response of a jacket platforms in regards to current engineering knowledge and variance jacket platforms configuration remains limited. The research aims to compare API procedure, i.e. the silhouette method for predicting wave-in-deck force with detailed component method. Simulation study has been carried out and evaluate the wave-in-deck forces on two fixed jacket platforms installed in South China Sea using SESAM Software (GeniE and USFOS) by DNV GL and to quantify wave forces and the effect of wave-in-deck in terms of RSR on the jacket platforms. The results indicate that detailed component method has smaller reduction of RSR for platform A by 2.65 and platform B by 9.25 whereas silhouette methodâs reduction by 18.58 and 32.91 respectively. Â© 2020, Springer Nature Singapore Pte Ltd.